Exploring the conceptual model of digital ecosystem - Dong, Hai; Hussain, Farookh; Chang, Elizabeth (IEEE, 2007)
Digital Ecosystem, as a neoteric terminology, has emerged along with the appearance of Business Ecosystem which is a form of naturally existing business network of small and medium enterprises. However, few researches have been found in the field of defining digital ecosystem. In this paper, by means of ontology technology as our research methodology, we propose to develop a conceptual model for digital ecosystem. By introducing an innovative ontological notation system, we create the hierarchical framework of digital ecosystem form up to down, based on the related theories form Digital Ecosystem and Business Intelligence Institute.